1995
DOI: 10.1101/gad.9.15.1846
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic phenotype induced by overexpression of wild-type gas3/PMP22: its relation to the demyelinating peripheral neuropathy CMT1A.

Abstract: Although the Gas3/PMP22 protein is expressed at highest levels in differentiated Schwann cells, its presence, albeit at lower levels, in non-neuronal tissues and in NIH-3T3 growth-arrested fibroblasts argues for a more general function of this protein that is uncoupled to myelin structure. We show that gas3/PMP22 overexpression in NIH-3T3 growing cells leads to an apoptotic-like phenotype, which is suppressed by antioxidants and characterized by typical membrane blebbing, rounding up, and chromatin condensatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
3
4

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(153 citation statements)
references
References 39 publications
5
141
3
4
Order By: Relevance
“…1 hese results indicate tnat PMP22 participates in fundamental mechanisms of cell growth and further demonstrate that there are cell type-specific differences in the ability to tolerate en hanced levels of PMP22. In agreement with these findings, C. Schneider provided further evidence for a link between PMP22 overexpression and programmed cell death using an expression plasmid microinjection paradigm (Fabbretti et aL, 1995). In contrast to PMP22, the overexpression, of Po protein causes no apoptosis, indicating marked differences in growth-related cellu lar functions of myelin proteins.…”
Section: 8supporting
confidence: 67%
“…1 hese results indicate tnat PMP22 participates in fundamental mechanisms of cell growth and further demonstrate that there are cell type-specific differences in the ability to tolerate en hanced levels of PMP22. In agreement with these findings, C. Schneider provided further evidence for a link between PMP22 overexpression and programmed cell death using an expression plasmid microinjection paradigm (Fabbretti et aL, 1995). In contrast to PMP22, the overexpression, of Po protein causes no apoptosis, indicating marked differences in growth-related cellu lar functions of myelin proteins.…”
Section: 8supporting
confidence: 67%
“…8 Similar to Perp, PMP22 and the EMPs can induce caspase-dependent apoptosis upon overexpression in cell culture. 9,10 However, members of the PMP22 family have also been implicated with other cellular processes, such as membrane trafficking and cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that Gas2 and Gas3 are involved in regulating different aspects of apoptosis. Gas2, after a specific proteolytic processing, regulates microfilament changes during apoptosis while Gas3 can trigger apoptosis when overexpressed in NIH3T3 cells (Fabbretti et al, 1995).…”
Section: Gas2 and Gas3 Proteins Levels In Balb/c Cell Lines Transformmentioning
confidence: 99%
“…Removal of this domain triggers a potent cell shape and microfilament re-organizing activity in Gas2 . On the other side gas3 overexpression, by itself, is able to trigger apoptosis in NIH3T3 cells (Fabbretti et al, 1995).…”
Section: Introductionmentioning
confidence: 99%